Sexual Dimorphism in Transcriptional and Functional Glucocorticoid Effects on Mouse Skeletal Muscle - Li, Sheng; Schönke, Milena; Buurstede, Jacobus C.; Moll, Tijmen J.A.; Gentenaar, Max; Schilperoort, Maaike; Visser, Jenny A.; Kaikaew, Kasiphak; van de Vijver, Davy; Abbassi-Daloii, Tooba; Raz, Vered; Aartsma-Rus, Annemieke; et al. (Frontiers in Endocrinology, 2022)
Muscle atrophy is common in patients with increased glucocorticoid exposure. Glucocorticoid effects are often sex-specific, and while different glucocorticoid responses between male and female subjects are reported, it is unclear why this is. In this study, we evaluated the effects of corticosterone and synthetic glucocorticoid treatment on muscle atrophy in male and female mice. We found that corticosterone treatment reduced grip strength in female mice only, whereas muscle mass was reduced in both sexes. Skeletal muscle transcriptional responses to corticosterone treatment were more pronounced and widespread in male mice. Synthetic glucocorticoid treatment reduced grip strength in both sexes, while female mice were more sensitive to muscle atrophy than male mice. To evaluate the role of androgens, chemically-castrated male mice were treated with synthetic glucocorticoids. We observed additively reduced muscle mass, but did not observe any interaction effects. Although sex differences in glucocorticoid responses in skeletal muscle are partly influenced by androgen signaling, further studies are warranted to fully delineate the underlying mechanisms.